The Impact of Epidemiological Trends and Guideline Adherence on Candidemia-Associated Mortality: A 14-Year Study in Northeastern Italy - Fabiana Dellai; Alberto Pagotto; Francesco Sbrana; Andrea Ripoli; Giacomo Danieli; Alberto Colombo; Denise D’Elia; Monica Geminiani; Simone Giuliano; Assunta Sartor; Carlo Tascini (Journal of Fungi)
Invasive candidiasis represents a major global health concern, with incidence and mortality rates expected to rise due to medical advancements and unavoidable risk factors. This retrospective, multicentric study was conducted in eight hospitals in a northeastern Italian region, enrolling adult patients diagnosed with candidemia from 1 January 2018 to 31 December 2022. Epidemiological trends and clinical characteristics were analyzed and compared to those from a prior regional study (2009–2011), allowing a fourteen-year comparative evaluation. A shift in species distribution was observed, with a decline in Candida albicans (from 65.7% to 57.8%) and a rise in non-albicans species, particularly the Candida parapsilosis complex (from 16.1% to 18.2%). Guideline adherence was assessed applying the EQUAL Candida score; scores ≥ than 11.5 were independently associated with improved in-hospital survival (HR 3.51, p < 0.001). Among individual score components, empiric echinocandin therapy and central venous catheter removal correlated with better outcomes. Centers with routine infectious disease (ID) consultations showed higher survival and adherence, reinforcing the value of specialist involvement. These findings support local epidemiological and management practice surveillance program adoption to address context-specific gaps, promote the adoption of best practices in Candida BSI management—as expanded ID specialist consultations and education programs—and, ultimately, reduce candidemia-related mortality rates.